Vibration assessment of the International Guadiana Bridge - Elsa Caetano (2005)
The paper describes the development of a monitoring program for a cable-stayed bridge and resumes the major dynamic properties identified from a series of test campaigns conducted on the bridge, which are also correlated with results from a numerical analysis. Some aspects of the current dynamic behavior of the bridge under ambient excitation are discussed, considering in particular the large cable vibrations that are frequently observed.